A REGISTER USED BY NETIZEN IN MARAH-MARAH COMMUNITY OF X (TWITTER) - Cecilia; Sonya Ayu Kumala (Bhumantara, 2026)
This study examines the linguistic registers used by netizens in the Marah-Marah Community of X (Twitter), an online space where users express anger and dissatisfaction regarding various issues. Dell Hymes’ (1972) Speaking Model provides the theoretical framework to classify and analyze registers within this community. A qualitative approach was employed to collect primary data consisting of posts, comments, and interactions during April 2025. The analysis identified 200 registers, of which 185 (90%) were informal and 15 (10%) were colloquial. Informal registers included slang, abbreviations, code-switching, emotive words, and emojis, reflecting intense emotions such as anger and frustration. Colloquial registers demonstrated regional and cultural nuances. The findings highlight that informal registers dominate emotional discourse in online communities, functioning as tools of identity construction, solidarity, and coping mechanisms. This study contributes to sociolinguistics by providing insights into how register variation reflects emotional expression and social bonding in digital environments.